EKSISTENSI PURA KAHYANGAN TIGA DI DESA ADAT PENARUKAN KECAMATAN KERAMBITAN KABUPATEN TABANAN - Dewa Made Sudiarta; Ni Gusti Ayu Agung Nerawati (Pangkaja: Jurnal Agama Hindu, 2023)
The temple is a sacred place for Hindus to worship and connect with Ida Sang Hyang Widhi and all its manifestations. Pura Kahyangan Tiga Penarukan has its own uniqueness compared to other places where Pura Puseh, Pura Desa or Pura Bale Agung, Pura Dalem including Prajapati are all in one place (one place). The arrangement of pelinggih at Kahyangan Tiga Penarukan temple does not use Meru but Gedong. The choice of location in the formation of Kahyangan Tiga temple has natural features that exist in the traditional village of Penarukan. Kahyangan Tiga can be established in nature or place provided that he must find a place marked by three criteria namely the  presence of dwara nets, double motherland, the presence of favorable land. From the above phenomena, Pura Kahyangan Tiga Penarukan needs further research, and the type of research is qualitative with data collection methods, namely: observation, interviews, literature studies and documentation. While the results obtained are: 1) What is the structure of Pura Kahyangan Tiga 2) What  is the function of Pura Kahyangan Tiga  (3) The hidden philosophical meaning of the existence of Pura Kahyangan Tiga. According to the results of this study, the existence of Kahyangan Tiga temple in Penarukan  traditional village is not only limited to divine values, but also has other meanings because of the understanding of the community, customs and culture of Penarukan as a temple.  Pura Kahyangan Tiga in Penarukan traditional village has only one site (area). Pura Kahyangan Tiga has several functions, namely religious functions and the function of unifying people. The hidden meanings in Kahyangan Tiga temple  are moral, aesthetic and a sense of harmony. Kahyangan Tiga Temple  has a very important role for the Penarukan community.